Influence of Fatigue on the Rapid Hamstring/Quadriceps Force Capacity in Soccer Players - Zhang, Qingshan; Morel, Baptiste; Trama, Robin; Hautier, Christophe A. (Frontiers in Physiology, 2021)
The objective of this study was to examine the effect of fatigue on maximal and rapid force capacities and muscular activation of the knee extensors and flexors. Seventeen professional soccer players volunteered to participate in this study. Peak torque (Tpeak) and rate of torque development (RTD) of knee flexor (90 °. s-1, -30 °. s-1) and extensor (90 °. s-1) muscles were measured before and after fatigue ( i.e., 30 maximal knee extension and flexion repetitions at 180 °s-1) performed on an isokinetic dynamometer. Hamstring to quadriceps peak strength and RTD ratios were calculated. Besides, using surface EMG, the mean level of activation (RMSmean), Rate of EMG Rise (RER), and EMG Frequency-Time maps were measured on quadriceps and hamstring muscles. Following fatigue, Tpeak, RTD, RER declined significantly in the two muscle groups (all p<0.05) without modification of RMSmean. No decrease in conventional and functional H/Q ratios was observed after fatigue except for a significant increase in the Hecc30/Qcon180 ratios (1.03 ± 0.19 vs. 1.36 ± 0.33, p < 0.001). Besides, the RTD H/Q ratios decreased significantly after fatigue, and the statistical parametric mapping analysis (SPM) performed on the EMG/angle curves, and EMG Frequency-Time maps showed that fatigue strongly influenced the muscle activation during the first 100 milliseconds of the movement, following the higher EMG frequency component shift toward the lower frequency component. Our results show that the reduction of RTD and RER during the first 100 milliseconds of the contraction after fatigue exercise makes more sense than any H/Q ratio modification in understanding injury risk in soccer players.